Optimasi Waktu Pelayanan Terminal Purabaya dengan Pendekatan Entropi Maksimum - Kuswandi, Imron (Department Industrial Engineering, University of Muhammadiyah Malang, 2008)
Â The main purpose in queue case was achieving equilibrium between service fees and the fees caused by the available waiting times. This case also happened on the queue system at Purabaya Terminal, Surabaya. In the one hand, the exceed service capacity preparation will cause the queue time. On the other hand, the less service capacity preparation will cause the bigger losses must be guaranteed by bus businessman because of not carrying a number of passengers. Cases at Purabaya Terminal were really general queue cases that can be solved by using the available queue theory. But which methodologically there were problems from the queue theory that has been available, in the queue theory that has been available frequently is less able to give real situation image from the observed system. This case was indicated by the happening several assumptions about the available probability distribution of certain system state in which this case will limit the real condition from the observed system. Because the conventional approach has weaknesses, this research used entropy approach. The entropy approach enables to handle the queue system by arrival rates which spread generally. Then, by entropy approach, it can be determined the optimal capacity service for the fast and limited bus armadas as follows: West Line I = 17 minutes 17 seconds, West Line II = 14 minutes 43 seconds, South Line = 13 minutes 21 seconds, East Line = 12 minutes 37 seconds, Madura Line = 2 hours 19 minutes, and Semarang Line = 1 hours 47 minutes.